Wide-Band Gain Enhancement of a Pyramidal Horn Antenna with a 3D-Printed Epsilon-Positive and Epsilon-Near-Zero Metamaterial Lens - Keskin, Nesem; AKŞİMŞEK, HÜSEYİN SİNAN; Turker Tokan, Nurhan (Cambridge University Press, 2021)
In this article, we present a simple, low-cost solution for the gain enhancement of a conventional pyramidal horn antenna using additive manufacturing. A flat, metamaterial lens consisting of three-layer metallic grid wire is implemented at the aperture of the horn. The lens is separated into two regions; namely epsilon-positive and epsilon-near-zero (ENZ) regions. The structure of the ENZ region is constructed accounting the variation of relative permittivity in the metamaterial. By the phase compensation property imparted by the metamaterial lens, more focused beams are obtained. The simulated and measured results clearly demonstrate that the metamaterial lens enhances the gain over an ultra-wide frequency band (10-18 GHz) compared to the conventional horn with the same physical size. A simple fabrication process using a 3D printer is introduced, and has been successfully applied. This result represents a remarkable achievement in this field, and may enable a comprehensive solution for satellite and radar systems as a high gain, compact, light-weighted, broadband radiator.
Keywords: Antenna Design; Epsilon-near-zero; Meta-materials and Photonic Bandgap Structures; Modeling and Measurements